2017
DOI: 10.1186/s12889-017-4641-9
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of contraceptive use and future contraceptive intentions of women attending child welfare clinics in urban Ghana

Abstract: BackgroundFamily planning is an integral component of maternal and child health services in Ghana. Although knowledge on contraception is universal and most women attend maternal and child health services, contraceptive use remains low among women after delivery. This study aimed to determine factors influencing current use and future contraceptive intentions of women who were attending child welfare clinics within 2 years of delivery in Sunyani Municipality, Ghana.MethodsWe conducted an analytical cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
42
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 17 publications
14
42
4
1
Order By: Relevance
“…Therefore, there is a need for collaborated efforts by government and its partners to make contraceptives affordable to all women. Our finding is consistent with studies done in other countries which also reported that women who were working were more likely to use contraceptive [ 29 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, there is a need for collaborated efforts by government and its partners to make contraceptives affordable to all women. Our finding is consistent with studies done in other countries which also reported that women who were working were more likely to use contraceptive [ 29 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…An important finding is that only about one-fourth of adolescent wives in our sample reported ever having discussed contraception with their husbands and one-fifth of husbands reported these discussions, a prevalence lower than found in relevant recent studies in sub-Saharan Africa [ 22 , 30 32 ]. While research has shown that Nigerien women have in recent times exercised some amount of agency in FP [ 7 ], significant and persistent gender inequality [ 33 ] may bolster traditional gender roles, playing a large part in determining engagement in communication behaviors.…”
Section: Discussioncontrasting
confidence: 86%
“…The benefit of a voucher in facilitating early initiation of family planning in this trial was seen across all subgroups. Effect sizes, however, appeared bigger in certain subgroups, for example, women subscribing to a non-Catholic religion, those with parity more than 3, women aged 30 years and above, women who attended at least 4 prenatal visits, women with improved household income, and women with a previous history of modern family planning Family planning voucher and early initiation of postpartum contraceptive use use, which corroborates prior work demonstrating higher rates in use of contraception among such populations [49][50][51][52][53][54]. This may also be corroborated with observed reduction in reported fertility aspirations among the same postpartum WLWH with increasing age, parity, and previous use of modern family planning methods [9].…”
Section: Discussionsupporting
confidence: 79%